Online reputation and media social management in three star hotels - Nevado Timaná, Fiorella Lisbeth (2019)
In the present context, online reputation has become very important, so the hotel companies have been forced to create new strategies to manage areas of the network actively and continuously, since these allow them to communicate with your prospects for establishing closer relationships and so achieve a stronger reputation. This research aims to determine the strategic plan using the hotels to monitor their online reputation, taking as example the three-star hotels in Chiclayo’s city, that have a web presence. The research is qualitative type, with and emergent design, so we will focus on 07 three-star hotels in Chiclayo’s city. For data collection technique interview, which will be directed to the managers of establishments applies. Cameras and audio records were the instruments used. Datta processing was carried out in the word processor Microsoft Word 2010.